EDUKASI GIZI DAN PEMBENTUKAN PEER EDUCATOR REMAJA PUTRI SEBAGAI UPAYA MENINGKATKAN KEPATUHAN KONSUMSI TABLET TAMBAH DARAH PADA REMAJA PUTRI DI SMPN 11 KOTA BEKASI - Noerfitri, Noerfitri; Rohayati , Rohayati; Sartika, Arindah Nur; Hilal, Muhammad; Dewi, Felika Puspita; Astuti, Sani Zulfi; Rahmadhani, Nova (Jurnal Abdi Insani, 2024)
West Java Province has a higher prevalence of adolescent anemia compared to Indonesia, namely 41.5%. Research on 345 vocational school students in Bekasi showed that 31% suffered from anemia. The routine administration of blood supplement tablets (TTD) is a mandatory program to prevent anemia in adolescent girls. The activity of providing blood supplement tablets has not run optimally so it has not achieved the targets that have been set. Peer empowerment through peer educators can be done to encourage and monitor young women in the blood supplement tablet taking program. The aim of this service activity is to increase knowledge of anemia prevention and the ability of peer educators to provide education to their peers. This service program is called BELIA (Bekasi peduli anemia) which partners with SMPN 11 Bekasi City and Aren Jaya Health Center. The targets of BELIA activities are young women in grades 7 and 8, students of SMPN 11 Bekasi City. This activity includes education for 38 young women who were selected to become Duta Belia (peer educators), and practical activities to become Duta Belia using role play and practicum methods which took place on 9 and 10 September 2024. Based on the results of the previous Duta Belia knowledge assessment. and after education, it was discovered that as many as 16 questions (80%) had increased in terms of the number of participants who answered correctly. The highest increase was for questions regarding food or drinks that can inhibit iron absorption. Based on the analysis of the difference in scores before and after education, it is known that there was an increase in the median knowledge score of Duta Belia, namely 45 points before education to 75 points after education. Of the 38 Duta Belia, 97% experienced an increase in knowledge scores. This activity can provide benefits in increasing compliance with TTD consumption if there is a commitment from the Duta Belia who have been formed to continue to remind their peers about consuming TTD.